2015
DOI: 10.1186/s12875-015-0276-z
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with workplace violence in emergency primary health care: a focus group study

Abstract: BackgroundPrevention and management of workplace violence among health workers has been described in different health care settings. However, little is known about which phenomena the emergency primary health care (EPC) organization should attend to in their strategies for preventing and managing it. In the current study, we therefore explored how EPC personnel have dealt with threats and violence from visitors or patients, focusing on how organizational factors affected the incidents.MethodsA focus group stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 32 publications
1
55
0
3
Order By: Relevance
“…Several cross sectional surveys have been conducted in various parts of the world, but surprisingly, qualitative (perception) studies have scarcely been performed. 32,33,[41][42][43] The perception of young doctors has remained almost unexplored hitherto. To our knowledge this is the first qualitative study in India which has explored the perception of young (junior) doctors regarding health care work place violence.…”
Section: Discussionmentioning
confidence: 99%
“…Several cross sectional surveys have been conducted in various parts of the world, but surprisingly, qualitative (perception) studies have scarcely been performed. 32,33,[41][42][43] The perception of young doctors has remained almost unexplored hitherto. To our knowledge this is the first qualitative study in India which has explored the perception of young (junior) doctors regarding health care work place violence.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Un estudio reciente realizado en Noruega a través de grupos focales detectó 4 prioridades vinculadas con el sistema para ayudar en el manejo de la agresión: 1. minimizar el riesgo de trabajar solo; 2. estar preparado (tomar precauciones frente a los signos de alerta y estar capacitado); 3. reducir la diferencia entre las expectativas del paciente y lo que el sistema le puede ofrecer; y 4. el respaldo de las autoridades (especialmente, el seguimiento después del episodio). 25 Q u e r e m o s r e s a l t a r l a i m p o r t a n c i a d e reflexionar acerca de esta situación, ya que, por un lado, especialmente el personal de enfermería asume la agresión recibida como parte natural de la tarea y no reporta la mayoría de los casos. 26 Por otro lado, se aumenta la vigilancia o se restringe el acceso a los sectores críticos sin considerar, además, el rol de la interacción personal como generador de episodios de agresión.…”
Section: Discussionunclassified
“…Working alone increases the risk of WPV, and where the risk of violence is high, staff should not work alone (Morken, Johansen, & Alsaker, 2015;Wikman, 2014). Yet participants reported that risk assessment for home visiting services did not always reflect the true level of risk, putting staff in danger.…”
Section: Sufficient Resourcesmentioning
confidence: 99%